Manajemen Kompas dan Peningkatan Mutu Sekolah SD Negeri 02 Payakumbuh - Ideswal Ideswal (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2018)
The best practice is motivated by the task and function of the principal as an Educator, Manager, Administrator, Supervisor, Leadership, Innovator, and Motivator. Not all principals, especially in Elementary School (SD) in Payakumbuh perform tasks and functions so that the quality of education has not increased. The best practice is motivated by the task and function of the principal as an Educator, Manager, Administrator, Supervisor, Leadership, Innovator, and Motivator. Not all principals, especially in Elementary School (SD) in Payakumbuh perform tasks and functions so that the quality of education has not increased. The phenomenon that occurred in SD Negeri 02 Payakumbuh. Much effort is being made by schools to improve quality. The goal is to know the management of school management and know-how to empower the citizens of the school. Efforts taken to overcome the problem is to run the program Management KOMPAS (Communication and participation). The activities designed in this program are 1) Application of effective Communication Management, 2) Implementation of Participation Management. Activities in the program have an impact and result from the academic and non-academic aspects.